Islamic parenting education: Emotional stimulation of children in the family - Ririn Dwi Wiresti; Devi Vionitta Wibowo; Anggil Viyantini Kuswanto (At Turots: Jurnal Pendidikan Islam, 2025)
Positive Parenting in the Islamic perspective is the implementation of Islamic parenting that must be taught in the family environment. This is done to educate parents in educating and developing intellectual-based religious character. In the context of Nashih Ulwan provides many scientific ideas regarding Islamic parenting education to overcome problems that occur in education and parenting in the family environment. This writing aims to develop Islamic parenting education to contribute to parents to implement the Islamic parenting system to develop and instill positive characters based on positive emotional formation in the child's personality. The method used in this writing uses a literature study in qualitative research, namely the analysis of Abdullah Nashih Ulwan's theory of Islamic parenting which is analyzed from the implementation of Muslim family parenting to determine the stimulation of the development of emotional planting in children in the family. The results of the study state that Islamic parenting in stimulating children in the family is based on providing affection, care, character education, and instilling morality so that children appear confident in their social environment. There is a strategy to stimulate children's emotions in the family environment, through Islamic parenting education, namely the application of giving affection during care, character education in children's personalities, and becoming role models and wise and fair individuals when dealing with children's problems in the family environment.